Protective regulation of the ACE2/ACE gene expression by estrogen in human atrial tissue from elderly men. Issue 14 (August 2017) - Bukowska, A; Spiller, L; Wolke, C; Lendeckel, U; Weinert, S; Hoffmann, J; Bornfleth, P; Kutschka, I; Gardemann, A; Isermann, B; Goette, A
Data from animal experiments and clinical investigations suggest that components of the renin-angiotensin system are markedly affected by sex hormones. However, whether estrogen affects human atrial myocardium has not been investigated yet. In this study, we determined the effects of estrogen on key components of atrial renin-angiotensin system: angiotensin-converting enzyme, responsible for generation of angiotensin II and angiotensin-converting enzyme 2, counteracting majority of AngII effects, and different renin-angiotensin system receptors, AT1R, AT2R, and MAS. First, the expression levels of estrogen receptors mRNA were determined in right atrial appendages obtained from patients undergoing heart surgery. The amounts of estrogen receptor α and estrogen receptor β mRNA were similar between women ( n = 14) and men ( n = 10). Atrial tissue slices (350 µm) were prepared from male donors which were exposed to estrogen (1–100 nM; n = 21) or stimulated at 4 Hz for 24 h in the presence or absence of 100 nM estrogen ( n = 16), respectively. The administration of estrogen did not change mRNA levels of estrogen receptors, but activated MAP kinases, Erk1/2. Furthermore, estrogen increased the amounts of angiotensin-converting enzyme 2-mRNA (1.89 ± 0.23; P < 0.05) but reduced that of angiotensin-converting enzyme-mRNA (0.78 ± 0.07, P < 0.05). In addition, the transcript levels of AT2R and MAS were upregulated by estrogen. Pacing of tissue slices significantly increased the angiotensin-converting enzyme/angiotensin-converting enzyme 2 ratio at both the mRNA and protein level. During pacing, administration of estrogen substantially lowered the angiotensin-converting enzyme/angiotensin-converting enzyme 2 ratio at the transcript (0.92 ± 0.21 vs. 2.12 ± 0.27 at 4 Hz) and protein level (0.94 ± 0.20 vs. 2.14 ± 0.3 at 4 Hz). Moreover, estrogen elicited anti-inflammatory and anti-oxidative effects on renin-angiotensin system-associated downstream effectors such as pro-oxidative LOX-1 and pro-inflammatory ICAM-1. An antagonist of estrogen receptor α reversed these anti-inflammatory and anti-oxidative effects of estrogen significantly. Overall, our results demonstrated that estrogen modifies the local renin-angiotensin system homeostasis and achieves protective effects in atrial myocardium from elderly men. Impact statement: The present study demonstrates that estrogen affects the human atrial myocardium and mediates protective actions through estrogen receptors-(ER) dependent signaling. Estrogen substantially modulates the local RAS via downregulation of ACE and simultaneous upregulation of ACE2, AT2R and MAS expression levels. This is indicative of a shift of the classical RAS/ACE axis to the alternative, protective RAS/ACE2 axis. In support of this view, estrogen attenuated the expression of RAS-associated downstream effectors, LOX-1, and ICAM-1. A specific antagonist of ERα reversed the anti-inflammatory and anti-oxidative effects of estrogen in paced and non-paced atrial tissue slices. In summary, our data demonstrate the existence of protective effects of estrogen in atrial tissue from elderly men which are at least in part, mediated by the regulation of local RAS homeostasis.